PENGARUH LATIHAN H-MOVEMENT TERHADAP KELINCAHAN PADA PEMAIN SEPAKBOLA SSB RUMBAI PRATAMA PEKANBARU - Syahbani, Andri Syahbani; ', Slamet; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract This study was conducted to determine whether there are effects of exercise on the H-Movement  agility in football players so that when doing a game to get maximum results. This research is a form of research with experimental treatment (Experimental), with a population of players football SSB Rumbai Pratama Pekanbaru , in this study all population data of 16 people. The instruments used in this research is Illinois Agility Ran Test, Which aims to measure agility in changing direction quickly, data is processed with statistics, to the test normality of the test at significant level 0,05α lilifors. Hypothesis proposed, exercise effect of H-Movement To Agility.Based on t test analysis produces 12,5 Thitung and 1.753 Ttabel, its means Thitung>Ttabel. Based on analysis of statistical data, there are on Pree-test average was 17,84 and post-test average was 17,09, data is normal. Then, there is a Exercise Effect of H-Movement To Agility the player football SSB Rumbai Pratama Pekanbaru. Keywords: H-Movemen , Agility